الاحتياجات التدريبية للأخصائيين الاجتماعيين العاملين في المجال الطبي: دراسة ميدانية بالمستشفيات العامة الحكومية بمدينتي أبها وخميس مشيط - القحطاني، سعيد بن هادي بن سعيد; الشهراني، عائض بن سعد أبو نخاع (المؤسسة العربية للتربية والعلوم والآداب, 2023)
هدفت الدراسة إلى التعرف على الاحتياجات التدريبية (المعرفية - المهارية) للأخصائيين الاجتماعيين العاملين في المجال الطبي بالمستشفيات الحكومية بمحافظة أبها وخميس مشيط، وكذلك معرفة المعوقات التي تحول دون استفادة الأخصائيين الاجتماعيين في المجال الطبي من البرامج التدريبية، والتوصل إلى عدد من المقترحات للأخصائيين الاجتماعيين العاملين في المجال الطبي لتطوير الدورات التدريبية، وقد اعتمدت الدراسة على منهج المسح الاجتماعي بأسلوب العينة العمدية من (49) من الأخصائيين الاجتماعيين العاملين بالمستشفيات العامة الحكومية بمدينتي أبها وخميس مشيط، واستخدمت الاستبانة كأداة رئيسية لجمع بيانات الدراسة، وقد كشفت نتائج الدراسة أن نسبة 95.9% أبدوا الموافقة على وجود احتياجات تدريبية هي الاحتياج إلى معرفة المداخل التي تساعد في حل مشكلات المرضى، وأحتاج إلى معرفة مسببات بعض الأمراض المختلفة التي أتعامل معها في المجال الطبي، كما كشفت النتائج أن نسبة 89.5% يوافقون على وجود احتياجات تدريبية مهارية للأخصائيين الاجتماعيين العاملين في المجال الطبي مثل أنفذ المبادئ المهنية لتكوين علاقة مهنية مع المرضى، ولدي إلمام بمهارة الملاحظة كأسلوب من أساليب المقابلة، كما كشفت النتائج أن غالبية أفراد العينة لا يعلمون بنسبة 77.8% بوجود معوقات تحول دون استفادة الأخصائيين الاجتماعيين في المجال الطبي من البرامج التدريبية، وذلك وأهم هذه المعوقات عدم اهتمام إدارة المستشفى باختيار المدربين المتمكنين لتنفيذ الدورات، والتركيز على النواحي النظرية أكثر من العملية بالعملية التدريبية، ولا يتم تغطية احتياجاتي التدريبية من هذه البرامج. وقد أوصت الدراسة بضرورة مراعاة الاحتياجات التدريبية للأخصائيين الاجتماعيين المشاركين في البرامج التدريبية وذلك من خلال نوعية المعارف والمهارات والاتجاهات التي يحتاجون إليها. The study aimed to identify the training needs (knowledge skills) of social workers working in the medical field in government hospitals in Abha Governorate and Khamis Mushait, as well as to know the obstacles that prevent social workers in the medical field from benefiting from training programs, and to reach a number of proposals for social workers working in The medical field to develop training courses, and the study relied on the method of social survey in the method of deliberate sample of (49) social workers working in public hospitals in the cities of Abha and Khamis Mushait, and the questionnaire was used as a main tool for collecting the study data, and the results of the study revealed that 95.9% expressed approval The existence of training needs is the need to know the approaches that help in solving patients' problems, and I need to know the causes of some different diseases that I deal with in the medical field, and the results revealed that 89.5% agree that there are skilled training needs for social workers working in the medical field, such as I implement professional principles to form a professional relationship with patients, and I have an Elma The results revealed that the majority of respondents did not know, 77.8%, that there are obstacles that prevent social workers in the medical field from benefiting from training programs, and the most important of these obstacles is the lack of interest of the hospital's management in choosing capable trainers to implement the courses, and focusing on The theoretical aspects are more than the practical ones in the training process, and my training needs are not covered by these programs. The study recommended that the training needs of social workers participating in training programs should be taken into consideration through the quality of knowledge, skills and attitudes they need.
Keywords: الاحتياجات التدريبية -- المجالات الطبية -- المستشفيات الحكومية -- الأخصائيون الاجتماعيون